ANALISIS MIXING KODE PADA VIDEO YOUTUBE CHANNEL ATTA HALILINTAR - Rahmadi, Nizar; Nukhriyan, Nukhriyan (Pengelola Jurnal Politeknik Negeri Ketapang, 2025)
Sociolinguistics explores the relationship between language and society, recognizing that individuals use different language styles when interacting with one another. Given the many variations in language use, people often mix languages in their speech—a phenomenon known as code mixing in sociolinguistics. Code mixing is a common practice in many communities, including among well-known public figures. One notable example is Atta Halilintar, a popular Indonesian YouTuber with the largest subscriber base in Southeast Asia. This study examines the occurrence of code mixing in videos from Atta Halilintar’s YouTube channel. The research aims to identify the types and levels of code-mixing present in his content. This study employs a descriptive qualitative method, with the researcher serving as the primary instrument. Data collection is conducted using a documentation method, and content analysis is applied to examine code mixing. The study categorizes code mixing types based on Hoffman’s classification and assesses the levels of code mixing according to Suwito’s framework. The frequency and distribution of code mixing are then analyzed using Sudjiono’s formula. The findings reveal a total of 34 instances of code mixing in the analyzed videos. Among the types of code mixing, intra-sentential code mixing is the most frequent, while changes in pronunciation are the least common. Regarding levels of code mixing, the dominant level is at the word level, whereas repetition words and idioms appear the least.